Thank God it's natural : a distribution dilemma - Lecinski, Jim, (SAGE business cases., 2022)
Chris-Tia Donaldson was the CEO and founder of Thank God It's Natural (tgin), a specialty hair care line for women with naturally curly, kinky, or wavy hair types. By early 2019, Donaldson had built tgin into a national brand in the United States, with its products widely available at large retailers such as Walmart and Target, as well as in specialty beauty retail stores like Sally Beauty. One important beauty retailer still did not carry the brand, however: Ulta Beauty, a US chain of 1,196 brick-and-mortar beauty stores located predominantly in high-traffic shopping centers around the country. Ulta also had a robust online storefront in ulta.com and had cultivated a vibrant social media presence. On Donaldson's desk was an offer from Ulta Beauty to stock tgin for the first time. Should she commit to this deal, knowing she was setting aside other opportunities, such as e commerce, direct-to-consumer (DTC), and the pursuit of additional distribution channels? All things considered: Was this distribution agreement with Ulta really the best path forward for tgin?